Too Early to execute the strategic scenario planning: hyperbolic discounting and psychological biases of Indonesian SMEs' managers - Brahmana, Rayenda; Siregar, Widyana Verawaty; Hsb, Amawan (Emerald Group Publishing Limited, 2013)
Purpose – Using the hyperbolic discounting approach in qualitative manner, the purpose of this paper is to explore the linkage of the time preference bias towards the too early execution of strategic focused planning. The paper also investigates the role of psychological bias in explaining the early execution.